Edukacja demokratyczna według Hannah Arendt - Eliasz, Katarzyna (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
Among various modes of the vita activa considered by Hannah Arendt, the ability for action and particularly political action is the crucial one as it endows life with meaning and constitutes human freedom. The question I address in this essay is whether it is possible – according to Arendt – to create active citizenship by means of democratic education. In order to answer this question I consider three models of democratic education, two of which should be rejected if one agrees with Arendt’s assumptions. The third model, aimed at developing abilities to think critically, is the only one that can support those values, which are essential for a healthy democracy.